2022
DOI: 10.20944/preprints202201.0141.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of DNA Damage Response by SAM and HD Domain Containing Deoxynucleoside Triphosphate Triphosphohydrolase (SAMHD1) Determines Prognosis and Treatment Efficacy in Different Solid Tumor Types

Abstract: SAMHD1 is a deoxynucleotide triphosphate (dNTP) triphosphohydrolase with important roles in the control of cell proliferation and apoptosis, either through the regulation of intracellular dNTPs levels or the modulation of the DNA damage response. However, SAMHD1 role in cancer evolution is still unknown. We performed the first in-depth study of SAMHD1 role in advanced solid tumors, by analyzing samples of 128 patients treated with chemotherapy agents based on platinum derivatives and/or antimetabolites and dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…In the colorectal cancer, high expression SAMHD1 correlated with metastasis [30] and indicated poor prognosis of stage II patients [31]. Consistent with our results, Eudald Felip et al found that low expression of SAMHD1 was associated with a positive prognosis in breast, ovarian and non-small cell lung cancer patients [32].…”
Section: Discussionsupporting
confidence: 90%
“…In the colorectal cancer, high expression SAMHD1 correlated with metastasis [30] and indicated poor prognosis of stage II patients [31]. Consistent with our results, Eudald Felip et al found that low expression of SAMHD1 was associated with a positive prognosis in breast, ovarian and non-small cell lung cancer patients [32].…”
Section: Discussionsupporting
confidence: 90%
“…. IHC was performed routinely on all primary colon cancer samples, as previously described (26,27). All samples were fixed in 10% neutral buffered formalin at room temperature for 1 h and maintained at 4˚C with 30% saccharose overnight.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%